Bibliometric analysis of research trends in low-cost sensors for air pollution monitoring: innovations and future implications - Yuli Dwi Astanti; Berty Dwi Rahmawati; Dian Hudawan Santoso; Ahmad Taufiq Akbar (TELKA - Telekomunikasi Elektronika Komputasi dan Kontrol, 2026)
Air quality monitoring is imperative due to the substantial health and environmental ramifications of atmospheric contamination. The present study endeavors to examine prevailing research trends in low-cost sensors, which offer an efficacious and attainable approach to evaluating air quality. A meticulous bibliometric meta-analysis was executed using data from multiple academic databases to identify publication patterns, prominent authors, and influential institutions in this domain. The methodology entailed the analysis of publication counts, citation metrics, and collaboration networks to underscore the expansion and pertinence of low-cost sensor research. The analysis was executed using Biblioshiny software. The findings indicate a marked increase in publications over recent years, reflecting heightened interest and innovation in this area. The present analysis employed a set of 233 articles published between 2011 and 2025, with all data exclusively sourced from Scopus. This study underscores the potential of low-cost sensors to enhance air quality monitoring efforts, providing valuable insights for future research and policy development aimed at mitigating air pollution and its associated risks.